Food partitioning between the Mara (Dolichotis patagonum) and the introduced hare (Lepus europaeus) in the Monte desert, Argentina - Bonino, Never Antonio (1997)
In the semiarid Monte desert, Río Negro province, the mara (Dolichotis patagonum) and the European hare (Lepus europaeus), which was introduced about hundred years ago, today occur sympatrically, as in many regions of Argentina. The forage use of these herbivores was determined by fecal analysis in order to estimate food partitioning and the presumed interspecific nutritional competition. Microhistological analysis of the fecal plant remnants collected at three study sites proved a high overall similarity in diet for both species, primarily based on shrub consumption during summer and winter. However, annual and perennial grasses and forbs were also foraged, especially in spring. Though a trophic niche overlap of about 50% was calculated, it remains doubtful if the introduced hare has diminished the mara population.